Learn to live Existence, thought, trace in/of Derrida - Fernández Agis, Domingo (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
In this paper I approach the problem of the Nietzschean heritage in the thought of Jacques Derrida as a basis for raising the question of the footprint of the latter in current philosophy. For this, I approach the relationship between life and ideal of life, as both thought. Starting from this aspect, I pose the problem of the relationship between life and work, the question of personal identity, the assessment of thought as a critical activity and the question of the possibility of the impossible, which is central to Derridian thought. Through all this, I intend to highlight the enormous future projection that in my opinion Derrida’s work has.
Keywords: life; work; identity; critical thinking; possibility of the impossible; Derrida; Nietzsche